Study of physical settings of traditional markets regarding development feasibility - Ardhiansyah, Nicolaus Nino (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Borobudur Market cannot be separated from the existence of Borobudur Temple as the main tourist destination in Central Java. Borobudur Market is expected to be able to play a role as a tourist "point-of-interest", not just in the economic activities of the surrounding community. Magelang Regency, Central Java has quite a large distribution of traditional markets, so the Regional Government of Magelang Regency is committed to improving the quality of services and facilities at conventional markets. The Magelang Regency Government's numerous initiatives, such as market revitalization and research projects aimed in establishing traditional marketplaces there, demonstrate how this commitment is being carried out. The government of Magelang Regency is concerned on a number of marketplaces, including Borobudur Market. The public's prejudice of traditional markets, which are typically connected to slums, subpar service, and scant auxiliary facilities, is the largest obstacle facing Borobudur Market. Spatial planning, parking space accessibility, trader zoning, loading and unloading zones, and other issues are some of the issues at Borobudur Market. Using the Pasar Rakyat SNI variable, the analytical approach will map current issues. The various situations and current conditions of the Borobudur Market are signs that this market must immediately improve so that its role can transform from a traditional market to a tourist market that runs optimally.